Kepentingan Singapura pada Keamanan Siber di Asia Tenggara dalam Singapore International Cyber Week - Muhammad Fikry Anshori; Rizki Ananda Ramadhan (Universitas Padjadjaran, 2019)
This article describes the interest of Singapore in the cybersecurity of Southeast Asia by organizing Singapore International Cyber Week. This article uses the concept of interest based on constructivism. This article uses interpretive qualitative method. This article finds that Singapore interprets itself as “smart nation” and “cyberattack target” in Southeast Asia; Singapore’s objective interests are capacity building, awareness building, and norm formation on cybersecurity of Southeast Asia; and Singapore’s subjective interest is involving Southeast Asia nations in cybersecurity issue by organizing ASEAN Ministerial Conference on Cybersecurity, launching ASEAN Cyber Capacity Program, and initiating ASEAN-Singapore Cybersecurity Center of Excellence. Artikel ini bertujuan mendeskripsikan kepentingan yang dihadirkan ole Singapura pada keamanan siber di Asia Tenggara dengan menyelenggarakan Singapore International Cyber Week. Konsep yang digunakan adalah kepentingan berdasarkan konstruktivisme. Metode yang digunakan adalah kualitatif interpretatif. Artikel ini menemukan Singapura memaknai kondisi dirinya sebagai “smart nation” dan “target serangan siber” di Asia Tenggara; Singapura memiliki kepentingan objektif berupa pembangunan kapasitas, pembentukan kesadaran, dan pembentukan norma pada keamanan siber di Asia Tenggara; serta Singapura memiliki kepentingan subjektif berupa melibatkan negara-negara di Asia Tenggara dalam isu keamanan siber dengan penyelenggaraan ASEAN Ministerial Conference on Cybersecurity, peluncuran ASEAN Cyber Capacity Programme, dan penggagasan ASEAN-Singapore Cybersecurity Centre of Excellence.